Roles of Prostaglandins and Hydrogen Sulfide in an Outflow Model of the Porcine Ocular Anterior Segment Ex Vivo - Jenaye Robinson; Leah Bush; Anthonia Okolie; Fatima Muili; Sunny Ohia; Catherine Opere; Ya Fatou Njie Mbye (MDPI AG, 2024)
Background: Hydrogen sulfide (H2S)-releasing compounds can reduce intraocular pressure in normotensive rabbits by increasing aqueous humor (AH) outflow through the trabecular meshwork. In the present study, we investigated the contribution of endogenous H2S and the role of intramurally generated prostaglandins in the observed increase in AH outflow facility in an ex vivo porcine ocular anterior segment model. Material and Methods: Porcine ocular anterior segment explants were perfused with Dulbecco's Modified Eagle's Medium maintained at 37 °C and gassed with 5% CO2 and 95% air under an elevated pressure of 15 mmHg for four hours. Perfusates from the anterior segment explants were collected and immediately assayed for their H2S and prostaglandin E2 content. Results: Elevating perfusion pressure from 7.35 to 15 mm Hg significantly (p < 0.001) increased H2S concentration in the perfusate from 0.4 ± 0.1 to 67.6 ± 3.6 nM/µg protein. In the presence of an inhibitor of cystathionine ß-synthase/cystathionine γ-lyase, aminooxyacetic acid (AOAA, 30 µM), or an inhibitor of 3-mercaptopyruvate sulfurtransferase, α-ketobutyric acid (KBA, 1 mM), the effects of elevated pressure on H2S levels in the perfusate was significant (p < 0.001). Furthermore, flurbiprofen (30 µM) and indomethacin (10 µM) attenuated the elevated pressure-induced increase in H2S levels in the perfusate. Interestingly, elevating perfusion pressure had no significant effect on PGE2 concentrations in the perfusate. While the inhibition of H2S biosynthesis by AOAA or KBA did not affect PGE2 levels in perfusate, flurbiprofen (30 µM) caused a significant (p < 0.05) decrease in the concentration of PGE2 under conditions of elevated perfusion pressure. Conclusions: We conclude that the elevated perfusion pressure-induced increase in H2S concentrations depends upon the endogenous biosynthesis of H2S and intramurally produced prostaglandins in the porcine anterior segment explants. While the concentration of PGE2 in the perfusate under elevated perfusion pressure was unaffected by pretreatment with inhibitors of H2S biosynthesis, it was reduced in the presence of an inhibitor of cyclooxygenase.